2008
DOI: 10.1124/dmd.108.024521
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation of Benzodiazepines by CYP3A4

Abstract: ABSTRACT:Cytochrome P450 3A4 is the predominant isoform in liver, and it metabolizes more than 50% of the clinical drugs commonly used. However, CYP3A4 is also responsible for metabolic activation of drugs, leading to liver injury. Benzodiazepines are widely used as hypnotics and sedatives for anxiety, but some of them induce liver injury in humans. To clarify whether benzodiazepines are metabolically activated, 14 benzodiazepines were investigated for their cytotoxic effects on HepG2 cells treated with recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…[3,[10][11][12] Midazolam, alprazolam and triazolam ( Fig. 1) are mainly excreted in urine as glucuronides of the hydroxylated metabolites, where the α-hydroxy-metabolite predominates the 4-hydroxylation.…”
Section: Flubromazolam Was First Reported In Sweden In 2014 and Inclumentioning
confidence: 99%
“…[3,[10][11][12] Midazolam, alprazolam and triazolam ( Fig. 1) are mainly excreted in urine as glucuronides of the hydroxylated metabolites, where the α-hydroxy-metabolite predominates the 4-hydroxylation.…”
Section: Flubromazolam Was First Reported In Sweden In 2014 and Inclumentioning
confidence: 99%
“…64 The toxicity of nimesulide to hepatocytes has been previously observed 65,66 which is attributed mainly to the nitro group in its structure. 67 After reduction, NiNH 2 exhibits reduced toxicity than nimesulide in hepatocytes because nimesulide is a powerful protonophoretic uncoupler and NAD(P)H oxidant.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 99%
“…Vignati et al (2005) demonstrated, using HepG2 cells transiently transfected with CYP3A4, that reactive metabolites of various hepatotoxic drugs such as albendazole, flutamide, and troglitazone were produced by CYP3A4. Our previous study showed that benzodiazepines such as flunitrazepam and nimetazepam were metabolically activated by CYP3A4 by coincubation with HepG2 cells and CYP3A4 Supersomes (Mizuno et al, 2009). Thus, several in vitro studies demonstrated that P450 enzymes, especially CYP3A4, are involved in the cytotoxicities of various kinds of drugs.…”
Section: Introductionmentioning
confidence: 99%